2022
DOI: 10.3390/ijerph191811723
|View full text |Cite
|
Sign up to set email alerts
|

Appropriateness of Antibiotic Prescribing for Acute Conjunctivitis: A Cross-Sectional Study at a Specialist Eye Hospital in Ghana, 2021

Abstract: Most presentations of conjunctivitis are acute. Studies show that uncomplicated cases resolve within 14 days without medication. However, antibiotic prescription remains standard practice. With antimicrobial resistance becoming a public health concern, we undertook this study to assess antibiotic prescription patterns in managing acute conjunctivitis in an eye hospital in Ghana. We recorded 3708 conjunctivitis cases; 201 were entered as acute conjunctivitis in the electronic medical records (January to Decembe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 25 publications
(31 reference statements)
0
1
0
Order By: Relevance
“…limiting and serious complications are rare [2,3]. Antimicrobials are also used inappropriately in non-bacterial cases of conjunctivitis [6].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…limiting and serious complications are rare [2,3]. Antimicrobials are also used inappropriately in non-bacterial cases of conjunctivitis [6].…”
Section: Resultsmentioning
confidence: 99%
“…This study found that utilisation was prevalent among NZ children and began early in life. Though indications were not captured in the dataset used (which was a limitation of this analysis), it is possible that the high usage of chloramphenicol partially reflects its inappropriate use in non-infectious (such as allergic) and viral conjunctivitis, both highly prevalent conditions [5,6]. Although evidence of substantial clinical benefit is limited, topical antimicrobials are often prescribed in the management of acute bacterial conjunctivitis [2,3], which likely also contributes to the high usage of chloramphenicol.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Как показали различные исследования, нередко воспалительный процесс при конъюнктивите не требует проведения медикаментозной терапии, особенно при отсутствии выраженной клинической симптоматики, так как воспаление купируется самопроизвольно [14,15]. Кроме того, рациональное использование местных антибиотиков при лечении острого конъюнктивита поможет предотвратить устойчивость к противомикробным препаратам, а также обеспечит эффективное оказание медицинской помощи и снизит расходы для пациентов и системы здравоохранения [16]. Важно дифференцировать степень выраженности воспалительного процесса при назначении лекарственных средств, особенно в условиях повышения резистентности к антибактериальным препаратам, а также большого количества осложнений, связанных с применением стероидной противовоспалительной терапии и повышенного уровня развития аллергических реакций на лекарственные препараты [17,18].…”
Section: резюмеunclassified
“…This disease can be classified according to chronicity, the seriousness of the disorder, the implication of affected tissues, and etiology [ 5 ]. Regarding chronicity, conjunctivitis can be classified as acute, lasting up to four weeks, and chronic, with a duration of more than four weeks [ 6 ].…”
Section: Introductionmentioning
confidence: 99%